Critical success factors for electronic customer relationship management success adoption: Telecommunication companies case study - Anaam E.A.; Bakar K.A.A.; Satar N.S.M.; Hasan M.K.; Mohamed M.A.; Mohamed R.R. (Institute of Advanced Science Extension (IASE), 2023)
A systematic literature review has been conducted on the exiting E-CRM system and found that 70% of E-CRM projects do not meet their ultimate goals. Furthermore, more than 77% of E-CRM projects do not succeed in the company's objectives. Many telecommunication companies reported that the existing E-CRM systems face severe challenges, which hinder the E-CRM system's successful adoption. This study aims to report the literature review on the Critical Success Factors for E-CRM systems and identify the rate of failure for E-CRM adoption. The systematic literature review (SLR) method has been conducted by analyzing 210 articles between 2011 to 2021 from different databases collections of research papers. The study determines ECRM Critical Success Factors from three aspects: Technology, organization, and individual factors. The three main categories were analyzed as the effects of the issue on E-CRM success in telecommunication companies. The results show that the three aspects (technology, organization, and individual factors) have a significant effect on the successful adoption of E-CRM. 2021 The Authors.